English-Indonesian Translation Strategies for Offensive Language in the Subtitles of No Hard Feelings (2023): A Study of Jay's and Gottlieb's Taxonomies - Bayu Ade Prabowo; Rahmanti Asmarani (FKIP, Universitas Palangka Raya, 2026)
The growing consumption of English-language entertainment content through streaming platforms has made subtitles a crucial linguistic and cultural bridge, particularly in handling offensive language (swearing), which is pragmatic and highly context-sensitive in nature. This study aims to identify the types of offensive language based on Timothy Jay's (1992) taxonomy and the translation strategies based on Henrik Gottlieb's (1992) taxonomy in the subtitles of the film No Hard Feelings (2023), as well as to map the relationship pattern between the two. The study employs a qualitative-descriptive method with a content-analysis approach applied to 111 pairs of English-Indonesian subtitles containing offensive language, matched by timestamp and manually verified against sentence context. The results show that the Vulgarity (51.4%) and Obscenity (32.4%) categories are the most dominant in the data, while the Euphemization strategy dominates the translations (76.6%), followed by Omission/Condensation (12.6%) and Equivalent/Neutral Transfer (10.8%). Cross-tabulation reveals that Vulgarity is most often handled through Euphemization and Omission, Obscenity is consistently euphemized without ever being omitted, while Profanity tends to be transferred neutrally. These findings indicate that subtitle translators consistently prioritize Indonesian socio-cultural norms over pragmatic equivalence, particularly for sexual and explicit-swearing categories. This study contributes theoretically by demonstrating the productivity of combining the Jay and Gottlieb frameworks to analyze the type and strategy dimensions of offensive language simultaneously, and practically by providing a reference for subtitle translators in balancing fidelity of meaning with cultural appropriateness.